Naïve T-cell decline is a significant contributor to expression changes in ageing blood - Fraser, Cameron; Owen, Brady M. (Frontiers in Aging, 2024)
No clear consensus has emerged from the literature on the gene expression changes that occur in human whole blood with age. In this study we compared whole blood ageing genes from the published literature with data on gene specificity for leukocyte subtypes. Surprisingly we found that highly ranked ageing genes were predominantly expressed by naïve T cells, with limited expression from more common cell types. Highly ranked ageing genes were also more likely to have decreased expression with age. Taken together, it is plausible that much of the observed gene expression changes in whole blood is reflecting the decline in abundance of naïve T cells known to occur with age, rather than changes in transcription rates in common cell types. Correct attribution of the gene expression changes that occur with age is essential for understanding the underlying mechanisms.